Kebijakan Digitalisasi Rekam Medis: Tinjauan terhadap Peraturan Menteri Kesehatan Nomor 24 Tahun 2022 - Azmi Asyfia; Zaid; Devin Mahendika; Maryani Setyowati (EDUPEDIA Publisher, 2023)
Objective: This study aims to examine the Regulation of the Minister of Health Number 24 of 2022 concerning Medical Records, which regulates electronic medical records. Methods: This research is juridical research with a statutory approach. Thus, this study only analyzes the rules and regulations related to legal or policy issues related to the digitization of medical records. Results: The obligation of the Electronic Medical Record (EMR) in Indonesia has legal certainty with the ratification of the Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022 concerning Medical Records. This obligation has administrative consequences in the form of a written warning and/or recommendations for revocation or revocation of accreditation status for Health Service Facilities that commit violations. The provisions of this policy must go into effect no later than December 31, 2023. Conclusion: Three new things are regulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022: the electronic system of electronic medical records, activities for organizing electronic medical records, security, and protection of electronic medical record data.